2013
DOI: 10.17221/7031-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

O-serogroups, virulence genes of pathogenic Escherichia coli and Pulsed-field gel electrophoresis (PFGE) patterns of O149 isolates from diarrhoeic piglets in Korea

Abstract: ABSTRACT:Control of metabolic pathways is a major task of the somatotropic axis and its constituents. Insulinlike growth-factor binding proteins (IGFBPs) bind IGF-I and -II and act as carriers and regulators of their activities in blood, body fluids and tissues. Over two periods of physiological adaptation, this study investigated the binding pattern of IGF-I to IGFBPs in the plasma of 50 multiparous Holstein dairy cows and identified relationships with the hepatic mRNA abundance of IGFBPs and plasma IGF-I dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…VITEK II system (bioMéreiux, France) was used to identify suspected colonies as E. coli. To identify F4 and F18 gene, previously described PCR protocols was used (Byun et al, 2013). Of these strains, 91 strains were F4 positive, 181 strains were F18 positive, and 7 strains were both F4 and F18 positive.…”
Section: E Coli Strains Isolated From Piglets Suffering Enteric Colimentioning
confidence: 99%
See 1 more Smart Citation
“…VITEK II system (bioMéreiux, France) was used to identify suspected colonies as E. coli. To identify F4 and F18 gene, previously described PCR protocols was used (Byun et al, 2013). Of these strains, 91 strains were F4 positive, 181 strains were F18 positive, and 7 strains were both F4 and F18 positive.…”
Section: E Coli Strains Isolated From Piglets Suffering Enteric Colimentioning
confidence: 99%
“…Among these enterotoxins, LT and ST are related to enterotoxigenic E. coli (ETEC) which is a well-known cause of PWD. Stx2e is related to Shiga-toxin producing E. coli (STEC) known to play an important role in the development of ED (Byun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The other serogroups O60, O100, O116, O117, and O120 were reported from diarrheic piglets in Korea [13]. Serogroup O80 has been reported from 23.56 % of E. coli strains isolated from diarrheic piglets in Western China [14].…”
Section: Discussionmentioning
confidence: 99%
“…According to different virulence factors, E. coli strains are classified in different pathotypes or categories. Enterotoxigenic E. coli (ETEC) is the main diarrheagenic E. coli pathotype, which causes intestinal infections in newborn pigs (2,3,5,27). Enterotoxigenic E. coli strains possess two virulence factors: adhesins and enterotoxins.…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…In the Czech Republic, EAST1 was present in 277 out of 800 strains (34.6%) (27). In Korea, 48 out of 116 isolates (41.4%) were positive for EAST1 (3), and in China the percentage of EAST1 strains was slightly lower (31.5%) (13). In our studies, we also detected a high prevalence of the astA gene, which was found in 72 out of 120 (60%) E. coli isolates from diarrhoeic piglets.…”
Section: Tab 1 Pcr Primers Used For Enterotoxin and Fimbrial Gene Dmentioning
confidence: 99%